Student Ranking Based on Learning Assessment Using the Simplified PIPRECIA Method and CoCoSo Method - Sitna Hajar Hadad; Dedi Darwis; Arie Qurania; Ahmad Ari Aldino; Abhishek R Mehta; Yuri Rahmanto; Setiawansyah Setiawansyah (Journal of Computer System and Informatics (JoSYC), 2023)
The problems that occur in determining the best students based on the learning process of the assessment process are still based on the academic scores of students and have not considered the learning process carried out by students. This study aims to apply the Combined Compromise Solution (CoCoSo) method in ranking students based on learning assessment using criteria of academic progress, problem-solving ability, mastery of skills, independence, motivation and positive attitude, adaptability, and for weighting the criteria used to apply the Simplified PIPRECIA (Pivot Pairwise Relative Criteria Importance Assessment) weighting method. The Simplified PIPRECIA method is particularly useful in situations where there are diverse criteria to be considered and complex decisions must be made taking into account the preferences and interests of various stakeholders. The Combined Compromise Solution Method is useful when there are conflicts in various criteria that need to be considered in the decision-making process. With this approach, each criterion is weighted and carefully calculated, so that the resulting decisions reflect comprehensive considerations that can meet various requirements and constraints. Based on the results of student rankings based on assessments in learning in the table above, rank 1 was obtained by students with Student ID 1211313 with a final grade of 6.487, rank 2 was obtained by students with Student ID 1211316 with a final grade of 6.402, and rank 3 was obtained by students with Student ID 1211314 with a final grade of 5.814.